Zeolite synthesis

By preparing aluminosilicate zeolite catalyst at low temperatures at atmospheric pressure, and performing calcination and ion exchange, the problem of preparing high SAR value CHA zeolites under high temperature and high pressure in the prior art is solved, and efficient and economical catalyst production is achieved.

CN114728802BActive Publication Date: 2024-12-17BASF MOBILE EMISSIONS CATALYSTS LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202080078864.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-11-19
Filing Date
2020-11-18
Publication Date
2024-12-17
Estimated Expiration
2040-11-18

AI Technical Summary

Technical Problem

The prior art is difficult to prepare CHA zeolite catalysts with high silica to alumina ratio under mild conditions, and often require harsh autoclaves and high temperature hydrothermal conditions.

Method used

A reaction mixture containing an alumina source, a silica source and an organic structure guide agent is formed at atmospheric pressure at 100°C or lower, and crystallized by stirring a vessel to prepare an aluminosilicate zeolite catalyst with a high SAR value. , and calcination and ion exchange can be performed on this basis to form a metal-promoting zeolite catalyst.

Benefits of technology

The preparation of CHA zeolite catalyst with high SAR value under mild conditions is realized, which maintains catalytic activity, reduces production costs and equipment requirements, and avoids the use of autoclaves.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114728802B_ABST
    Figure CN114728802B_ABST
Patent Text Reader

Abstract

The present disclosure provides a method for synthesizing a zeolite having a silica to alumina ratio (SAR) of 10 or greater, the method comprising, for example: forming a reaction mixture comprising at least one alumina source, at least one silica source, and at least one organic structure directing agent, wherein the reaction mixture has a solids content of about 10% or greater; and crystallizing the reaction mixture at a temperature of 100° C. or less at atmospheric pressure to form the zeolite.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application claims the benefit of priority to U.S. Provisional Application No. 62 / 937,572, filed on November 19, 2019, the contents of which are incorporated herein by reference in their entirety.

[0002] The present disclosure relates generally to the field of selective catalytic reduction (SCR) catalysts, and to methods of making and using such catalysts to selectively reduce nitrogen oxides.

[0003] Diesel engine emissions include particulate matter (PM), nitrogen oxides (NO x ), unburned hydrocarbons (HC) and carbon monoxide (CO). NO x A term used to describe various chemical species of nitrogen oxides, including nitric oxide (NO) and nitrogen dioxide (NO 2 ) etc. The two main components of exhaust particulate matter are the soluble organic fraction (SOF) and the soot fraction. SOF condenses on the soot in the form of a layer and usually comes from unburned diesel and lubricating oil. Depending on the temperature of the exhaust, SOF can be present in diesel exhaust in the form of vapor or aerosol (i.e. fine droplets of liquid condensate). Soot is mainly composed of carbon particles. The HC content in the exhaust may vary depending on the engine type and operating parameters, but generally includes various short-chain hydrocarbons such as methane, ethylene, acetylene, propylene, etc.

[0004] Various methods have been used to treat NO x A process for reducing atmospheric pollution involves the catalytic reduction of nitrogen oxides. There are two processes: (1) non-selective reduction processes, in which carbon monoxide, hydrogen or hydrocarbons are used as reducing agents; and (2) selective reduction processes, in which ammonia or an ammonia precursor is used as the reducing agent. In the selective reduction method, a high degree of nitrogen oxide removal can be achieved with a small amount of reducing agent.

[0005] Ideally, under hydrothermal conditions, the catalyst used in the SCR process should be able to maintain good catalytic activity over a wide temperature range (e.g., 200° C. to 600° C. or higher). SCR catalysts are often exposed to high temperature hydrothermal conditions, such as during the regeneration of a soot filter, which is a component of an exhaust treatment system for removing particulates.

[0006] Molecular sieves such as zeolites have been used for SCR of nitrogen oxides with reductants such as ammonia, urea or hydrocarbons in the presence of oxygen. Zeolites are crystalline materials with fairly uniform pore sizes, ranging in diameter from about 3 to about 10 angstroms, depending on the type of zeolite and the type and amount of cations included in the zeolite. Zeolites with 8-membered ring pore openings and double-six-membered ring secondary building blocks (such as, for example, those with cage structures) are very suitable for use as SCR catalysts. A specific type of zeolite with these characteristics is chabazite (CHA), which is a small pore zeolite with an 8-membered ring pore opening (about 3.8 angstroms) that is accessible through its 3-dimensional porosity. The cage structure is formed by double six-ring building blocks connected by 4 rings. Molecular sieves having a CHA framework structure can be prepared, for example, according to the methods disclosed in US Pat. Nos. 4,503,024, 4,544,538 and 6,709,644 and "Verified Synthesis of Zeolites Second Edition", Elsevier 2001, p. 123, each of which is incorporated herein by reference.

[0007] Typical methods for preparing certain CHA zeolites (such as, for example, zeolites having SAR values ​​of 10 or greater) involve hydrothermal synthesis under relatively harsh conditions. For example, in the '538 patent cited above, the zeolite is prepared by hydrothermal crystallization under pressure, typically in an autoclave. Similarly, the '644 patent cited above describes a process for preparing CHA (SSZ-64) crystals by hydrothermal crystallization at autogenous pressures at temperatures between 100° C. and 200° C. over a period of, for example, about 3 days to about 20 days. Although less harsh conditions are known for preparing certain zeolites, these methods are generally limited to preparing zeolites having lower silica to alumina ratio (SAR) values.

[0008] Therefore, there is a need for alternative methods for producing CHA (and other zeolites) of varying SAR without the aforementioned harsh conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] In order to provide an understanding of certain embodiments of the present disclosure, reference is made to the accompanying drawings, which are not necessarily drawn to scale and in which reference numerals refer to components of exemplary embodiments of the present disclosure. The accompanying drawings are provided only as examples and should not be construed as limiting the scope of the present disclosure.

[0010] Figure 1A depicts a perspective view of a honeycomb-type substrate that may include a catalyst composition of the present disclosure;

[0011] Figure 1B Depicts relative to Figure 1A Zoom in and follow the Figure 1A A partial cross-sectional view taken through a plane of the end surface of the carrier, showing Figure 1A An enlarged view of the multiple airflow paths shown in ;

[0012] Figure 2 shows a cross-sectional view of a portion of a wall flow filter substrate;

[0013] Figure 3 A schematic diagram showing an embodiment of an emission treatment system utilizing the catalyst of the present disclosure;

[0014] Figure 4A and 4B Provides a 150rpm ( Figure 4A ) and 350rpm( Figure 4B X-ray diffraction (XRD) pattern of a sample collected during crystallization at 97° C. in a stirred reflux vessel;

[0015] Figure 5A (scale bar: 5 μm) and 5B (scale bar: 500 nm) provide micrographs of CHA crystallized at 97°C in a stirred reflux vessel at 350 rpm; and

[0016] Figure 6 The SCR performance of selected samples from the following experimental section is plotted.

[0017] The present disclosure provides a method for synthesizing zeolites using less harsh conditions than those commonly used to produce, for example, CHA zeolites with a high silica to alumina (SAR) ratio. Specifically, the methods outlined herein can allow such production to be carried out at lower temperatures and / or at correspondingly lower temperatures. Advantageously, the disclosed process can be carried out in a simple stirred vessel (e.g., at atmospheric pressure) without the need for autogenous pressure. The present disclosure further provides the corresponding zeolite products thus prepared, as well as emission treatment systems and waste gas treatment methods utilizing the zeolite products.

[0018] These and other features, aspects and advantages of the present disclosure will become apparent from the detailed description below and the accompanying drawings, which will be briefly described below. Unless the context clearly stipulates otherwise, the present disclosure includes any combination of two, three, four or more embodiments and any combination of two, three, four or more features or elements set forth in the present disclosure, regardless of whether such features or elements are explicitly combined in the specific embodiment description herein. The present disclosure is intended to be interpreted as a whole, so that unless the context clearly stipulates otherwise, any separable features or elements of the present disclosure in any of the various aspects and embodiments of the present disclosure should be considered to be combinable. Other aspects and advantages of the present disclosure will become apparent from the following description.

[0019] The present disclosure is not limited to the details of the construction or process steps set forth in the following description. The present disclosure can have other embodiments and can be practiced or executed in various ways. It should be understood that the exemplary embodiments described herein are merely illustrations of the principles and applications of the present disclosure. It will be apparent to those skilled in the art that various modifications and variations may be made to the method and apparatus of the present disclosure without departing from the spirit and scope of the present disclosure. Therefore, it is intended that the present disclosure include modifications and variations within the scope of the appended claims and their equivalents.

[0020] In one aspect of the present disclosure, there is provided a method for synthesizing an aluminosilicate zeolite having a silica to alumina ratio (SAR) of 10 or greater, the method comprising: i) forming a reaction mixture comprising at least one alumina source, at least one silica source, and at least one organic structure directing agent, wherein the reaction mixture has a solids content of about 10% or greater (such as, for example, by weight); and ii) crystallizing the reaction mixture at a temperature of 100° C. or less in a container open to the atmosphere to form the aluminosilicate zeolite.

[0021] Described method can be used to provide various types of aluminosilicate zeolite products.For example, in some embodiments, described aluminosilicate zeolite comprises zeolite with 8 ring pore sizes.In certain embodiments, described aluminosilicate zeolite comprises zeolite with the framework containing double six rings (D6r) subunit.In certain embodiments, described aluminosilicate zeolite comprises zeolite with the framework of the combination selected from AEI, AFX, CHA, LEV, AFT, EAB, KFI, SAT, TSC, SAV, ERI, LTA and any of the foregoing.In certain embodiments, described aluminosilicate zeolite comprises zeolite with CHA crystalline framework.

[0022] For example, in some embodiments, the aluminosilicate zeolite comprises at least one zeolite having an 8-ring pore size. In some embodiments, the aluminosilicate zeolite comprises at least one zeolite having a framework containing double six-ring (D6r) subunits. In some embodiments, the aluminosilicate zeolite comprises at least one zeolite having a framework selected from AEI, AFX, CHA, LEV, AFT, EAB, KFI, SAT, TSC, SAV, ERI and LTA. In some embodiments, the aluminosilicate zeolite comprises at least one zeolite having a CHA crystalline framework.

[0023] In some embodiments, the method provides an aluminosilicate zeolite having a relatively high silica to alumina ratio (SAR) value, but the method is not limited thereto. In some embodiments, the aluminosilicate zeolite has a SAR of 15 or greater. In some embodiments, the aluminosilicate zeolite has a SAR of 20 or greater. In some embodiments, the aluminosilicate zeolite has a SAR of 10 to 30.

[0024] In some embodiments, the solid content of the reaction mixture is about 15% or more by weight. The at least one alumina source of the reaction mixture can vary, and in some embodiments comprises a zeolite, such as, for example, a zeolite having a FAU, LTL, LTA or MOR crystalline framework. In some embodiments, the at least one alumina source comprises a zeolite having a FAU crystalline framework in the form of zeolite Y. The at least one organic structure directing agent can also vary, and in some embodiments, the at least one organic structure directing agent is a quaternary ammonium salt having a substituent selected from a combination of alkyl substituents, aromatic substituents, and any of the foregoing items. In some embodiments, the at least one organic structure directing agent is a quaternary ammonium salt having at least one substituent selected from a combination of alkyl substituents, aromatic substituents, and any of the foregoing items. A non-limiting example of the at least one organic structure directing agent is tetramethylpiperidinium. The at least one silica source can also vary, and in some embodiments, the at least one silica source comprises an alkali metal silicate solution.

[0025] The parameters of the disclosed method can vary. For example, when performing the crystallization step, the temperature can vary, such as in some embodiments, wherein the crystallization step is performed at a temperature of about 95° C. to 100° C. In some embodiments, the disclosed method does not require the crystallization step to be performed in an autoclave. In some embodiments, the crystallization step is performed in a stirred vessel equipped with a reflux condenser. It may be advantageous to stir the reaction mixture, and in some embodiments, the crystallization step is performed under stirring.

[0026] In some embodiments, the methods provided herein include one or more additional method steps. For example, in some embodiments, the method may further include calcining the aluminosilicate zeolite to form a H + Form or Na + In some embodiments, the method may further include ion exchanging the aluminosilicate zeolite with a promoter metal to form an ion exchanged zeolite catalyst. In some embodiments, the method may further include ion exchanging the calcined zeolite with a promoter ion to form an ion exchanged zeolite catalyst. Such promoter metals may vary and may be, for example, Fe or Cu.

[0027] definition:

[0028] With respect to terms used in this disclosure, the following definitions are provided.

[0029] Throughout this specification, references to "one embodiment," "certain embodiments," "one or more embodiments," or "an embodiment" mean that a particular feature, structure, material, or characteristic described in connection with the embodiment is included in at least one embodiment of the present disclosure. Thus, phrases such as "in one or more embodiments," "certain embodiments," "in an embodiment," or "in an embodiment" that appear in different places throughout this specification do not necessarily refer to the same embodiment of the present disclosure. Furthermore, in one or more embodiments, the particular features, structures, materials, or characteristics may be combined in any suitable manner.

[0030] The articles "a" and "an" are used herein to refer to one or to more than one (ie, to at least one) of the grammatical object of the article.

[0031] Any ranges recited herein are inclusive, ie, unless otherwise stated, the endpoints are included within the stated range.

[0032] Throughout this specification, the term "about" is used to describe and explain small fluctuations. For example, the term "about" can refer to less than or equal to ±5%, such as less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.2%, less than or equal to ±0.1%, or less than or equal to ±0.05%. Whether or not explicitly stated, all numerical values ​​herein are modified by the term "about". Values ​​modified by the term "about" include specific values. For example, "about 5.0" includes 5.0.

[0033] The term "catalyst" or "catalyst material" or "catalytic material" refers to a material that promotes a reaction.

[0034] As used herein, the term "catalytic article" refers to an element used to promote a desired reaction. For example, the catalytic article can include a washcoat layer containing a catalytic material (such as, for example, a catalyst composition) on a substrate (eg, a honeycomb substrate).

[0035] As used herein, the term "washcoat" has its ordinary meaning in the art, i.e., a thin, adherent coating of a catalytic material or other material applied to a support substrate material (such as a honeycomb-type support member), the thin, adherent coating being sufficiently porous to allow the passage of a gas stream to be treated. As understood in the art, a washcoat can be obtained from a dispersion of particles in a slurry, which can be applied to a substrate, dried, and calcined to provide a porous washcoat.

[0036] As used herein, the term "substrate" refers to a monolithic material upon which a catalyst material is disposed, typically in the form of a washcoat.

[0037] As used herein, the term "stream" broadly refers to any combination of flowing gases that may contain solid or liquid particulate matter. As used herein, the term "gaseous stream" or "exhaust stream" means a stream of gaseous components (such as, for example, the exhaust gas of an engine) that may contain entrained non-gaseous components such as liquid droplets, solid particles, etc. The exhaust gas stream of the engine may further contain combustion products, products of incomplete combustion, nitrogen oxides, combustible and / or carbonaceous particulate matter (soot), and unreacted oxygen and nitrogen.

[0038] As used herein, the terms "particulate filter" and "soot filter" refer to filters designed to remove particulate matter, such as soot, from an exhaust gas stream.

[0039] As used herein, the term "BET surface area" has its ordinary meaning, i.e., refers to the surface area of ​​a 2 The Brunauer-Emmett-Teller method for determining surface area by adsorption can also be used, as will be appreciated by one of ordinary skill in the art. 2 Adsorption or desorption experiments are performed to determine the pore diameter and pore volume.

[0040] As used herein, "support" in the context of a catalytic material or catalyst washcoat refers to a material that receives a catalyst (including, for example, a noble metal, stabilizers, promoters, binders, etc.) by precipitation, association, dispersion, impregnation or other suitable means.

[0041] As used herein, the term "selective catalytic reduction" (SCR) refers to the reduction of nitrogen oxides to dinitrogen (N 2 As used herein, the term "nitrogen oxides" or "NO x ” stands for oxides of nitrogen. The SCR process uses the catalytic reduction of nitrogen oxides with ammonia to form nitrogen and water, typically according to the following reaction:

[0042] 4NO+4NH 3 +O 2 →4N 2 +6H 2 O(Standard SCR reaction)

[0043] 2NO 2 +4NH 3 →3N 2 +6H 2 O(Slow SCR reaction)

[0044] NO+NO 2 +2NH3 →2N 2 +3H 2 O(fast SCR response)

[0045] As used herein, the term "zeolite" refers to a specific example of a molecular sieve, comprising silicon atoms and aluminum atoms. Zeolites are substantially crystalline materials having relatively uniform pore sizes ranging from about 3 to about 10 angstroms in diameter, depending on the type of zeolite and the type and amount of cations included in the zeolite lattice.

[0046] Reference herein to an "aluminosilicate zeolite" framework type limits the material to molecular sieves that do not include phosphorus or other metals substituted in the framework. However, it should be understood that as used herein, "aluminosilicate zeolite" does not include aluminophosphate materials such as, for example, SAPO, ALPO and MeAPO materials, and the broader term "zeolite" is intended to include aluminosilicates and aluminophosphates.

[0047] Zeolite CHA framework type molecular sieves, otherwise referred to herein as "CHA zeolites," include zeolite groups having the following approximate formula: (Ca, Na 2 ,K 2 ,Mg)Al 2 Si 4 O 12 6H 2 O (such as, for example, hydrated calcium aluminosilicate). Three synthetic forms of zeolite CHA-framework type molecular sieves were described by DW Breck in "Zeolite Molecular Sieves" (published by John Wiley & Sons in 1973), which is incorporated herein by reference. The three synthetic forms reported by Breck are: zeolite KG, which is described in "J. Chem. Soc." (page 2822 (1956), Barrer et al.); zeolite D, which is described in British Patent No. 868,846 (1961); and zeolite R, which is described in U.S. Patent No. 3,030,181, each of which is incorporated herein by reference. The synthesis of another synthetic form of zeolite CHA-framework type, SSZ-13, is described in U.S. Patent No. 4,544,538, which is incorporated herein by reference.

[0048] As used herein, the term "promoting" refers to a metal component (such as, for example, a "promoter metal") that is intentionally added to a molecular sieve material that is completely different from the impurities inherent in the molecular sieve. Therefore, the promoter is intentionally added to enhance the activity of the catalyst compared to a catalyst without an intentionally added promoter. In order to promote the selective catalytic reduction of nitrogen oxides in the presence of ammonia, in one or more embodiments, one or more suitable metals are independently exchanged into the molecular sieve.

[0049] Example Embodiments

[0050] Without limitation, some embodiments of the present disclosure include:

[0051] 1. A method for synthesizing an aluminosilicate zeolite having a silica to alumina ratio (SAR) of 10 or more, the method comprising:

[0052] forming a reaction mixture comprising at least one alumina source, at least one silica source, and at least one organic structure directing agent, wherein the reaction mixture has a solids content of about 10% or more; and

[0053] The reaction mixture is crystallized at a temperature of about 100°C or less in a vessel open to the atmosphere to form the aluminosilicate zeolite.

[0054] 2. The method of embodiment 1, wherein the aluminosilicate zeolite comprises a zeolite having a pore size of 8 rings.

[0055] 3. The method of embodiment 1 or 2, wherein the aluminosilicate zeolite comprises a zeolite having a framework containing double six-ring (D6r) subunits.

[0056] 4. The method of any one of embodiments 1 to 3, wherein the aluminosilicate zeolite comprises a zeolite having a framework selected from AEI, AFX, CHA, LEV, AFT, EAB, KFI, SAT, TSC, SAV, ERI, LTA, and combinations of any of the foregoing.

[0057] 5. The method of any one of embodiments 1 to 4, wherein the aluminosilicate zeolite comprises a zeolite having a CHA crystalline framework.

[0058] 6. The method of any one of embodiments 1 to 5, wherein the aluminosilicate zeolite has a SAR of 15 or greater.

[0059] 7. The method of any one of embodiments 1 to 6, wherein the aluminosilicate zeolite has a SAR of 20 or greater.

[0060] 8. The method of any one of embodiments 1 to 5, wherein the aluminosilicate zeolite has a SAR of 10 to 30.

[0061] 9. The method of any one of embodiments 1 to 8 wherein the solids content of the reaction mixture is about 15% or greater.

[0062] 10. The method of any one of embodiments 1 to 9, wherein the at least one alumina source comprises a zeolite having a FAU, LTL, LTA, or MOR crystalline framework.

[0063] 11. The method of embodiment 10, wherein the zeolite having a FAU crystalline framework is zeolite Y.

[0064] 12. The method of any one of embodiments 1 to 11, wherein the at least one organic structure directing agent is a quaternary ammonium salt having at least one substituent selected from an alkyl substituent, an aromatic substituent, and a combination of any of the foregoing.

[0065] 13. The method of any one of embodiments 1 to 12, wherein the at least one organic structure directing agent is tetramethylpiperidinium.

[0066] 14. The method of any one of embodiments 1 to 13, wherein the temperature ranges from about 95°C to about 100°C.

[0067] 15. The method of any one of embodiments 1 to 14, wherein the vessel is a stirred vessel equipped with a reflux condenser.

[0068] 16. The method of any one of embodiments 1 to 15, wherein crystallizing the reaction mixture is performed under stirring.

[0069] 17. The method of any one of embodiments 1 to 16, wherein the at least one silica source comprises an alkali metal silicate solution.

[0070] 18. The method of any one of embodiments 1 to 17, further comprising calcining the aluminosilicate zeolite to form a + Form or Na + The calcined zeolite is in the form of.

[0071] 19. The method of embodiment 18, further comprising ion exchanging the calcined zeolite with a promoter metal to form an ion-exchanged zeolite catalyst.

[0072] 20. The method of any one of embodiments 1 to 17, further comprising ion exchanging the aluminosilicate zeolite with a promoter metal to form an ion-exchanged zeolite catalyst.

[0073] 21. The method of embodiment 19 or 20, wherein the promoter metal is Fe or Cu.

[0074] 22. A substrate comprising a metal-promoted zeolite catalyst composition prepared by the method of any one of embodiments 18 to 21.

[0075] 23. The substrate of embodiment 22, wherein the metal-promoted zeolite catalyst composition is coated on the substrate.

[0076] 24. The substrate of embodiment 23, wherein the metal-promoted zeolite catalyst composition is coated on the substrate in the form of a washcoat.

[0077] 25. The substrate of embodiment 24, wherein the washcoat layer comprises a binder selected from the group consisting of silica, alumina, titania, zirconia, ceria, and combinations of any of the foregoing.

[0078] 26. The substrate of embodiment 25, wherein the loading of the binder is from about 0.1 wt.% to about 10 wt.% based on the weight of the washcoat layer.

[0079] 27. The substrate of any one of embodiments 22 to 26, wherein the substrate is selected from a flow-through honeycomb monolith and a particulate filter.

[0080] 28. The substrate according to any one of embodiments 22 to 27, wherein the substrate is a ceramic or metal having a honeycomb structure.

[0081] 29. The substrate of any one of embodiments 22 to 27, wherein the substrate is a gasoline particulate filter or a soot filter.

[0082] 30. The substrate of any one of embodiments 22 to 29, comprising one or more catalyst layers on the inlet and / or outlet walls of the substrate.

[0083] 31. The substrate of any one of embodiments 22 to 30, comprising a combination of at least two catalyst layers on the inlet and / or outlet walls of the substrate.

[0084] 32. An exhaust treatment system comprising an engine and a catalyst composition prepared by the method of any one of embodiments 18 to 21.

[0085] 33. The exhaust treatment system of embodiment 32, wherein the engine is a lead combustion engine.

[0086] 34. The exhaust treatment system of embodiment 32 or 33, wherein the engine is a diesel engine or a lean burn gasoline engine.

[0087] 35. A method of treating an exhaust gas stream of an engine, the method comprising:

[0088] placing a catalyst comprising a metal-exchanged zeolite prepared by the method of any one of Examples 18 to 21 downstream of the engine; and

[0089] The exhaust gas stream of the engine is passed through the catalyst.

[0090] 36. The method of embodiment 35, wherein the engine is a lead combustion engine.

[0091] 37. The method of embodiment 35 or 36, wherein the engine is a diesel engine or a lean burn gasoline engine.

[0092] 38. The method of any one of embodiments 35 to 37, further comprising placing an additional catalyst component downstream of the engine.

[0093] In some embodiments, the disclosed zeolites are promoted with promoter metals selected from alkali metals, alkaline earth metals, transition metals (which are selected from Group IIIB, Group IVB, Group VB, Group VIB, Group VIIB, Group VIIIB, Group IB, and Group IIB), Group IIIA elements, Group IVA elements, lanthanides, actinides, and combinations of any of the foregoing. In some embodiments, promoter metals (such as, for example, further promoter metals) that can be used to prepare the promoted zeolites of the disclosed catalyst compositions include, but are not limited to, copper (Cu), cobalt (Co), nickel (Ni), lanthanum (La), manganese (Mn), iron (Fe), vanadium (V), silver (Ag), cerium (Ce), neodymium (Nd), praseodymium (Pr), titanium (Ti), chromium (Cr), zinc (Zn), tin (Sn), niobium (Nb), molybdenum (Mo), hafnium (Hf), yttrium (Y), tungsten (W), and combinations of any of the foregoing. In one or more embodiments, the promoter metal content, calculated as oxide, is independently about 0.01 wt.% to about 15 wt.%, about 0.5 wt.% to about 12 wt.%, or about 1.0 wt.% to about 10 wt.%, based on the total weight of the corresponding calcined zeolite (including the promoter metal), on a volatile-free basis. In some embodiments, the promoter metal is copper or iron.

[0094] The promoter metal can be exchanged into the zeolite by a liquid phase exchange process, wherein soluble metal ions (e.g., one or more soluble metal ions) are exchanged with protons or ammonium or sodium ions (e.g., one or more ions independently selected from protons, ammonium or sodium ions) associated with the zeolite. The exchange can also be performed by a solid state method, wherein solid particles of promoter metal oxide or metal salt are mixed with zeolite powder and treated at a specific temperature and gas environment that may or may not contain steam. The exchange process can also be accomplished by an in-situ process during slurry preparation, wherein fine metal oxide particles are suspended in a zeolite slurry under conditions suitable for solid-liquid interaction.

[0095] In one aspect, the present disclosure provides a method for forming zeolites under relatively mild conditions. It has been surprisingly found that even zeolites with high SAR values ​​(eg, SAR values ​​of 10 or more) can be crystallized under such conditions, as will be outlined below.

[0096] In some embodiments, the methods of the present disclosure comprise forming a reaction mixture comprising at least one alumina source (which includes a zeolite), at least one silica source, at least one organic structure directing agent, and optionally a secondary alkali metal cation source. The secondary alkali metal cation source can increase the alkali metal content of the reaction mixture. In some embodiments, the reaction mixture is provided under alkaline aqueous conditions. The ratios of the various components, particularly OH:SiO 2 Ratio and Na / SiO 2 The ratio can be adjusted, for example, by adding an acid source (such as, for example, sulfuric acid) and / or a sodium source (such as, for example, sodium sulfate).

[0097] The at least one silica source can vary, and is typically selected from a source comprising an alkali silicate solution and / or colloidal silica. The alkali metal, if present in at least one silica source, can be, for example, lithium, sodium, potassium, rubidium, cesium, or francium. In certain embodiments, the alkali metal is sodium or potassium (such as, for example, when the at least one silica source comprises sodium silicate or potassium silicate). When the at least one silica source comprises an alkali silicate, the individual metal (M) / Si molar ratio is at least about 0.4, or at least about 0.5, or at least about 0.6, or at least about 0.7, or at least about 0.8, wherein the range of non-limiting examples is from about 0.4 to about 1.2, or from about 0.6 to about 1.0, or from about 0.7 to about 0.9.

[0098] The zeolite included in the at least one alumina source may vary and will include various zeolite materials known in the art, such as, for example, various aluminosilicate zeolites. In certain embodiments, a zeolite having a FAU crystal structure is used, which is formed by a 12-ring structure and has about Channels. Non-limiting examples of such zeolites include faujasite, zeolite X, zeolite Y, LZ-210, and SAPO-37. Such zeolites are characterized by a 3-dimensional pore structure in which the pores are perpendicular to each other in the x, y, and z planes and have secondary building blocks 4, 6, and 6-6. Example SARs of bulk FAU zeolite materials range from about 3 to about 6, and the unit cell size range as determined by XRD is typically 24.35 to 24.65. Zeolite Y can be used in certain embodiments of the present disclosure. FAU zeolites can be in alkali metal form (such as, for example, Na + In a specific embodiment, the FAU zeolite is in the sodium form and contains about 2.5% to about 13% by weight of Na 2 O.

[0099] A non-limiting example of an organic structure directing agent for this synthesis is adamantyl trimethyl ammonium hydroxide, but other amines and / or quaternary ammonium salts may be substituted or added. Non-limiting examples include quaternary ammonium cations having substituents (such as, for example, one or more substituents) selected from alkyl, adamantyl, cyclohexyl, aromatic, and combinations of any of the foregoing. Additional non-limiting examples of organic structure directing agents include cyclohexyl trimethyl ammonium, benzyl trimethyl ammonium, and dimethyl pyridinium hydroxide.

[0100] Hydroxyl ions are the only essential mineralizer required in the reaction mixture, and the amount of hydroxide required to achieve the above ratios can be provided solely by the alkali metal silicate solution and, to a lesser extent, by the source of organic structure directing agent. If desired, the hydroxide ion content can be supplemented with an additional hydroxide ion source such as NaOH or KOH.

[0101] In some embodiments of the present disclosure, the reaction does not require the use of high pressures (such as, for example, reactions in autoclaves) as are typically required to produce various zeolites. As mentioned above, it is known that some zeolites can be produced without such harsh conditions, but it is generally understood that these harsh conditions are required to prepare zeolites with higher SAR values ​​(such as, for example, about 10 or more).

[0102] Thus, the disclosed methods generally comprise crystallizing the reaction mixture in the absence of applied pressure (such as, for example, at atmospheric pressure). For example, in certain embodiments, the crystallization reaction can be carried out in a container open to air (such as, for example, a container equipped with a reflux condenser). The method may involve heating the reaction mixture, wherein a non-limiting example of the reaction temperature is in the range of about 100° C. to about 160° C. (e.g., about 110° C. to about 160° C.).

[0103] In some embodiments, higher temperatures can result in a greater percentage of crystallization (i.e., greater conversion to product), all other parameters being equal. It has also been observed that the crystallization rate increases with the molar ratio of water to silica (i.e., H 2 O / SiO 2 The solid content of the zeolite gel is defined in the following way:

[0104] Solid content% = (Al in gel 2 O 3 moles of equivalent) × (101.96 g / mol) + (SiO in gel 2 moles of equivalent) × (60.08 g / mol)) × 100 / (total mass of gel)

[0105] By adjusting the solids content of the reaction mixture and the crystallization temperature, it was surprisingly found that a suitable degree of crystallization can be achieved at atmospheric pressure. Typical reaction times may vary depending on, for example, solids content and temperature, but are generally between about 30 hours and about 3 days.

[0106] In some embodiments, the precipitate may be prepared at atmospheric pressure and at a temperature of about 110° C. or higher at a relatively high solids content (e.g., about 15 or less H 2 O / SiO 2 In some embodiments, the crystallization can be carried out at atmospheric pressure and at a lower solid content (e.g., H > 15). 2 O / SiO 2 Ratios, such as about 15 to about 30) with correspondingly higher reaction temperatures (such as, for example, about 130°C or higher) can achieve about 50% or more crystallization. By further increasing the temperature and / or solid content, higher crystallization percentages (such as, for example, greater than 90%) can be achieved. For example, in some embodiments, at a temperature of at least about 120°C, for a H ratio of about 15 or less, 2 O / SiO 2 In some embodiments, for a reaction mixture having a higher solid content (e.g., H > 15), greater than 90% crystallization can be achieved. 2 O / SiO 2 Ratios, such as about 15 to about 30) but with an increased temperature relative to the previous examples (such as, for example, a temperature of about 140° C. or higher), can achieve greater than 90% crystallization.

[0107] Optionally, the product can be centrifuged. Organic additives can be used to help handle and separate the solid product. Spray drying is an optional step in product processing. The solid zeolite product thus obtained can be heat treated or calcined in air or nitrogen. Typical calcination temperatures range from about 400°C to about 850°C (such as, for example, about 500°C to about 700°C) over a period of about 1 to about 10 hours. After the initial calcination, the zeolite product is typically primarily in the alkali metal form (such as, for example, Na + Optionally, single or multiple ammonia ion exchanges may be used to generate the NH 4 + form, which is optionally further calcined to form H + form.

[0108] In certain embodiments, the zeolite is further ion exchanged with a promoter metal to form a metal-promoted zeolite catalyst. For example, copper or iron can be ion exchanged to form a copper or iron exchanged zeolite. Conventional methods can be used to carry out ion exchange. For example, in some embodiments, copper can be ion exchanged using copper oxide or copper acetate. The copper loading obtained can be defined, for example, based on a Cu / Al molar ratio, and can be, for example, about 0.2 to about 0.5 Cu / Al.

[0109] In some embodiments, the zeolite crystals produced by the disclosed crystallization can be about 80% to about 99% crystalline or about 90% to about 97% crystalline. In some embodiments, the method can be used to prepare a zeolite product with a CHA structure. However, it is not limited thereto. In some embodiments, the disclosed method can be used to produce aluminosilicate zeolite seeds with an 8-ring pore size, which have a structure selected from the combination of AEI, AFX, CHA, LEV, AFT, EAB, KFI, SAT, TSC, SAV, ERI, LTA and any of the foregoing items. In some embodiments, the method can be used to produce ZSM-5 zeolite.

[0110] The zeolite product can be characterized by a SAR range. As noted, in some embodiments, the disclosed method can be used to produce zeolites with a range of SAR values; however, this is particularly meaningful in producing zeolites with higher SAR values, because these zeolites have not been prepared under mild conditions to date. Therefore, although the method is widely applicable, in certain embodiments, the method is used to produce a zeolite product with a SAR of about 10 or greater, about 12 or greater, about 15 or greater, or about 20 or greater, such as, for example, a product with a SAR of about 10 to about 30, about 12 to about 30, about 15 to about 30, about 18 to about 30, or about 20 to about 30.

[0111] In certain embodiments, the metal-promoted zeolite material prepared according to the methods outlined herein can be characterized by SCR activity at various temperatures. In specific embodiments, the metal-promoted zeolite as provided herein exhibits similar SCR activity at various temperatures compared to similar metal-promoted zeolites prepared by conventional methods (i.e., those requiring high pressure). Specifically, the disclosed methods can provide a metal-promoted zeolite material characterized by SCR activity after a thermal aging treatment (e.g., at about 650°C (HDD) or at about 800°C (LDD)), wherein the NO of the metal-promoted zeolite material of the present disclosure is characterized at one or both of exhaust gas temperatures of about 200°C and about 600°C. x The conversion percentage of NO in the comparative metal-promoted zeolite materials with the same metal loading x The comparative zeolite is prepared using a comparative process as described in the Examples (eg, Sample B) within about 10% or about 20% of the conversion percentage. For example, the comparative metal-promoted zeolite material can be a zeolite material made using a reaction mixture that crystallizes under autogenous pressure.

[0112] Substrate

[0113] In one or more embodiments, the metal-promoted zeolite catalyst composition provided as described herein is placed on a substrate. Washcoat layer is formed in the following manner: a slurry of a catalyst containing a specific solid content (e.g., about 30% to about 90% by weight) is prepared in a liquid, and then the slurry is applied to a substrate and dried to provide a washcoat layer. The washcoat layer containing the metal-promoted molecular sieve as provided herein can optionally include a binder selected from a combination of silicon dioxide, aluminum oxide, titanium dioxide, zirconium oxide, ceria and any of the foregoing items. By the weight of the washcoat layer, the loading of the binder is generally about 0.1wt.% to about 10wt.%.

[0114] In one or more embodiments, the substrate is selected from a flow-through honeycomb monolith and a particulate filter, and the catalytic material is applied to the substrate as a washcoat.

[0115] Figure 1A and 1B An exemplary substrate 2 in the form of a flow-through substrate coated with a catalyst composition as described herein is depicted. Figure 1A , the exemplary substrate 2 has a cylindrical shape and a cylindrical outer surface 4, an upstream end face 6 and a corresponding downstream end face 8, the downstream end face being identical to the upstream end face 6. A plurality of thin parallel airflow passages 10 are formed in the substrate 2. Figure 1BAs shown, the flow passage 10 is formed by the wall 12 and extends through the substrate 2 from the upstream end face 6 to the downstream end face 8, and the passage 10 is unobstructed to allow a fluid (such as, for example, airflow) to flow longitudinally through the substrate 2 via its airflow passage 10. Figure 1B As can be more easily seen in FIG. 1 , the wall 12 is sized and configured so that the gas flow passage 10 has a substantially regular polygonal shape. As shown, the catalyst composition can be applied in multiple different layers if desired. In the illustrated embodiment, the catalyst composition consists of a discrete bottom layer 14 adhered to the wall 12 of the support member and a second discrete top layer 16 coated on the bottom layer 14. The present disclosure can be practiced with one or more (e.g., 2, 3, or 4) catalyst layers and is not limited to Figure 1B A two-layer embodiment is depicted.

[0116] In one or more embodiments, the substrate is a ceramic or metal having a honeycomb structure. Any suitable substrate can be used, such as, for example, a monolithic substrate type having a thin parallel gas flow passage extending from the inlet or outlet face of the substrate through which the passage is open to the fluid flowing therethrough. A passage that is substantially a straight path from its fluid inlet to its fluid outlet is defined by a wall coated with a catalytic material as a washcoat layer so that the gas flowing through the passage contacts the catalytic material. The flow passage of the monolithic substrate is a thin-walled channel that can have any suitable cross-sectional shape and size, such as, for example, a trapezoid, a rectangle, a square, a sinusoidal curve, a hexagon, an ellipse, a circle, etc. Such a structure can contain about 60 to about 900 or more gas inlet openings (i.e., cells) per square inch of cross section.

[0117] The ceramic substrate can be made of any suitable refractory material, such as, for example, cordierite, cordierite-α-alumina, silicon nitride, zircon mullite, spodumene, alumina-silicon dioxide-magnesium oxide, zirconium silicate, sillimanite, magnesium silicate, zircon, petalite, α-alumina, aluminosilicate, etc. The substrate that can be used for the catalyst of the embodiment of the present disclosure can also be metallic in nature, and can be composed of one or more metals or metal alloys. The metal substrate can include any metal substrate, such as, for example, those metal substrates with openings or "punch-outs" in the channel wall. The metal substrate can be used in various shapes (such as, for example, pellets, corrugated plates or monolithic forms). Non-limiting examples of metal substrates include heat-resistant base metal alloys, such as those alloys in which iron is the basic or main component. Such alloys may contain one or more elements selected from nickel, chromium and aluminum, and the total amount of these metals may comprise at least about 15 wt.% of the alloy, for example about 10 wt.% to about 25 wt.% chromium, about 1 wt.% to about 8 wt.% aluminum and about 0 wt.% to about 20 wt.% nickel, in each case based on the weight of the substrate.

[0118] In one or more embodiments where the substrate is a particulate filter, the particulate filter can be selected from a gasoline particulate filter or a soot filter. The particulate filter includes but is not limited to a honeycomb wall flow filter, a partial filtration filter, a wire mesh filter, a wound fiber filter, a sintered metal filter, and a foam filter. In a specific embodiment, the particulate filter is a catalytic soot filter (CSF). The catalytic CSF comprises a substrate such as coated with a catalyst composition as provided herein.

[0119] A wall-flow substrate that can be used to support the catalyst material of one or more embodiments can have a plurality of thin, substantially parallel gas flow passages extending along the longitudinal axis of the substrate. In some embodiments, each passage is blocked at one end of the substrate body, with alternating passages blocked at opposite end faces. Such monolithic substrates can contain up to about 900 or more flow passages (or "cells") per square inch of cross section, but a much smaller number can be used. For example, the substrate can have about 7 to about 600, more typically about 100 to about 400 cells per square inch ("cpsi"). The porous wall-flow filter used in the embodiments of the present disclosure can be characterized in that the porous wall-flow filter has or contains platinum group metals on the wall. The catalytic material can be present alone on the inlet side of the substrate wall, alone on the outlet side, on both the inlet side and the outlet side, or the wall itself can be composed of catalytic material in whole or in part. In another embodiment, the substrate can include one or more catalyst layers on the inlet and / or outlet walls of the substrate and a combination of at least two catalyst layers.

[0120] like Figure 2 As shown, the exemplary substrate has a plurality of passages 52. The passages are tubularly closed by the inner wall 53 of the filter substrate. The substrate has an inlet end 54 and an outlet end 56. Alternating passages are plugged at the inlet end with inlet plugs 58 and at the outlet end with outlet plugs 60 to form an opposing checkerboard pattern at the inlet 54 and outlet 56. Gas flow 62 enters through the unplugged channel inlet 64, is blocked by the outlet plug 60, and diffuses through the channel wall 53 (which is porous) to the outlet side 66. The gas cannot pass back to the inlet side of the wall because of the inlet plug 58. The porous wall flow filter used in the present disclosure can be characterized by having one or more catalytic materials on the wall of the substrate.

[0121] Exhaust gas treatment system

[0122] A further aspect of the present disclosure relates to an exhaust treatment system. In one or more embodiments, the exhaust treatment system comprises an engine (such as, for example, a lean burn engine, such as, for example, a diesel engine or a lean burn gasoline engine) and a catalyst composition of the present disclosure downstream of the engine.

[0123] Figure 3 An exemplary emission treatment system is depicted in , which depicts a schematic diagram of an emission treatment system 20. As shown, the emission treatment system may include a plurality of catalyst components connected in series downstream of an engine 22 (e.g., a lean-burn gasoline engine). At least one catalyst component may be an SCR catalyst of the present disclosure. The catalyst composition provided according to the present disclosure may be combined with a plurality of additional catalyst materials and may be placed in various positions compared to the additional catalyst materials. Figure 3 Five catalyst components 24, 26, 28, 30, 32 are depicted in series; however, the total number of catalyst components may vary, and five assemblies is merely a non-limiting example.

[0124] Without limitation, Table 1 shows various exhaust gas treatment system configurations for one or more embodiments. Note that each catalyst is connected to the next catalyst by an exhaust conduit such that the engine is upstream of catalyst A, catalyst A is upstream of catalyst B, catalyst B is upstream of catalyst C, catalyst C is upstream of catalyst D, and catalyst D is upstream of catalyst E (when present). References to components AE in the table may be the same as Figure 3 The same reference numbers are used for cross-references.

[0125] The DOC catalysts mentioned in Table 1 may be any catalyst conventionally used to reduce carbon monoxide (CO) and hydrocarbon (HC) pollutants in engine exhaust, and may comprise, for example, a platinum group metal (PGM) supported on a refractory metal oxide support such as, for example, alumina.

[0126] The LNT catalysts mentioned in Table 1 can be conventionally used as NO x any catalyst that can contain NO x Adsorbent composition comprising base metal oxide (BaO, MgO, CeO 2 etc.) and platinum group metals (such as, for example, Pt and Rh) for catalyzing NO oxidation and reduction.

[0127] Table 1. Example configuration

[0128] Component A Component B Component C Component D Component E DOC DPF SCR Optional AMOx - DOC SCRoF Optional AMOx - - DOC LNT SCRoF SCR Optional AMOx DOC LNT SCR Optional AMOx - DOC SCRoF SCR Optional AMOx -

[0129] The DPF mentioned in the table refers to a diesel particulate filter, which may consist of a wall-flow filter suitable for filtering particulate matter in exhaust gas.

[0130] The SCR mentioned in the table refers to an SCR catalyst, which may include an SCR catalyst composition comprising a metal exchange zeolite as described herein. The SCRoF (or SCR on a filter) mentioned refers to a particulate or soot filter (such as, for example, a wall flow filter), which may include an SCR catalyst composition provided herein. When both SCR and SCRoF are present, one or both may include an SCR catalyst provided herein, or one of the catalysts may include a conventional SCR catalyst. The emission treatment system may optionally include an injector positioned upstream of the SCR catalyst and suitable for injecting ammonia or an ammonia precursor (such as, for example, urea) into the exhaust gas stream.

[0131] AMOx, as referred to in the table, refers to an ammonia oxidation catalyst that can be provided downstream of the metal-exchanged zeolite-containing catalyst described herein to remove any escaped ammonia from the exhaust treatment system. In certain embodiments, the AMOx catalyst may include a PGM component. In one or more embodiments, the AMOx catalyst may include an undercoat layer and a topcoat layer, the undercoat layer including a PGM component, and the topcoat layer having SCR functionality.

[0132] As will be appreciated by those skilled in the art, any one or more of components A, B, C, D or E may be disposed on a particulate filter (such as, for example, a wall flow filter, etc.), or disposed on a flow-through honeycomb substrate in the configurations listed in Table 1. In one or more embodiments, the engine exhaust system comprises one or more catalyst compositions that are mounted at a location near the engine (in a close coupled location, CC), and additional catalyst compositions at a location below the substrate (in an underfloor location, UF).

[0133] Methods for treating engine exhaust

[0134] Another aspect of the present disclosure relates to a method for treating an exhaust gas stream of an engine (such as, for example, a lean burn engine). The method may include placing a catalyst comprising a metal exchanged zeolite prepared according to one or more embodiments of the present disclosure downstream of the engine and allowing the exhaust gas stream of the engine to flow through the catalyst. In one or more embodiments, the method further includes placing an additional catalyst component downstream of the engine as described above.

[0135] The present disclosure will now be described with reference to the following examples.

[0136] Examples

[0137] First, at various temperatures and various solid contents (H 2 O / SiO 2) to evaluate whether any crystallization could be observed at atmospheric pressure to form CHA product. Trimethyladamantyl ammonium hydroxide (TMadaOH) was used as an organic structure directing agent (OSDA), sodium silicate was used as a silica source, and Na-FAU was used as an alumina source.

[0138] SiO 2 :0.0219Al 2 O 3 :0.095TMAda + :0.84Na + :0.52OH - :11.7-33.6H 2 O

[0139] The OH / SiO ratio was adjusted by adding sulfuric acid and sodium sulfate, respectively. 2 and Na / SiO 2 ratio, and the following standard order of addition was used: H 2 O, NaOH, Na 2 SO 4 , H 2 SO 4 , Na-FAU, sodium silicate. The initial temperature study for 15 h crystallization time (Table 2) was conducted in a stirred autoclave (150 revolutions per minute (rpm)) and shows that the rate of CHA formation increases with H at all temperatures. 2 O / SiO 2 It is noteworthy that after crystallization at 100 °C, the gel with the highest solid content (H 2 O / SiO 2 =11.7) was detected in the gel.

[0140] Table 2. Phase composition after crystallization in 300 mL autoclave (15 hours, 150 rpm)

[0141]

[0142] Crystallization of the latter was subsequently attempted in a stirred glass vessel (150 or 350 rpm) with a reflux condenser at 97° C. Samples were periodically removed during the crystallization and analyzed by XRD as described below.

[0143] Two experiments were performed to evaluate the possibility of properly preparing such CHA zeolites by stirring at different rpm values ​​at atmospheric pressure. The diffraction patterns of these samples from the two crystallization experiments are shown in Figure 4A and 4B Middle: At 150rpm ( Figure 4A ) and at 350 rpm ( Figure 4B At 150 rpm, crystallization of CHA started after 45 hours and was complete after 93 hours at temperature. No other phases or amorphous materials were observed in the sample except FAU and CHA. When the stirring speed was increased to 350 rpm, complete conversion of FAU was achieved between 45 and 65 hours at 97°C. Micrographs of the final CHA product (SAR=20) obtained from the gel crystallized at 350 rpm are shown in Figure 5A and 5B The material showed high crystallinity (95% CHA) and correspondingly high surface area (ZSA = 560 m 2 / g,MSA=40mm 2 / g).

[0144] The prepared CHA product from 150 rpm crystallization was calcined (540° C.) to remove OSDA and then ammonium exchanged. 2 O'NH 4 + Calcination (450°C) to produce H + CuO was introduced to give a CuO loading of 4.6 wt.% (Sample A). It should be noted that ambient pressure crystallization (97°C for 72 to 100 hours) of conventional CHA zeolite gels, which are known to produce SAR 20 CHA products under hydrothermal conditions (140 to 170°C for 15 to 30 hours), did not produce a crystalline product.

[0145] A comparative sample (Comparative Sample B) was prepared by hydrothermal crystallization (170°C, 30 hours). The gel (referred to as "Comparative Gel") was prepared using the following composition (without the zeolite alumina source), wherein aluminum triisopropoxide and colloidal silica were used as alumina and silica sources, respectively.

[0146] SiO 2 :0.0506Al 2 O 3 :0.07TMAda + :0.13Na + :0.2OH - :11.6H 2 O

[0147] The comparative sample was then calcined, ammonium exchanged, calcined, and ion exchanged with CuO (same as sample A) to give crystalline SAR=20 CHA with 5.1 wt.% CuO loading.

[0148] The catalytic coating containing Sample A and Comparative Sample B, alumina and zirconia binder was placed on a honeycomb ceramic monolith with a cell density of 400 cpsi and a wall thickness of 6 mils by a washcoat process. The coated monolith was dried at 130°C and calcined at about 550°C for 1 hour. The coating process provided 2.2 g / in 3 The catalyst loading was 5% alumina and 5% zirconia binder. 2 The coated monoliths were hydrothermally aged at 650°C for 50 h (HDD) in the presence of O / air. -1 At a space velocity based on gas volume per hour, under pseudo-steady-state conditions, 1000ppm NO, 1000ppm NH 3 , 10% O 2 , 10% H 2 O. Residue N 2 The NO of samples aged at 650°C was measured in a gas mixture with a temperature ramp rate of 2.5°C / min from 175°C to 600°C. x Conversion.

[0149] The NOx conversion at 175°C and 600°C after aging at 650°C for the coated catalyst comprising Sample A and the coated catalyst comprising Comparative Sample B showed a decrease of Figure 6 As shown, slightly lower but similar performance after HDD aging is observed for Sample A compared to Comparative Sample B, and this difference can be attributed to the lower CuO content of Sample A.

[0150] It is obvious to those of ordinary skill in the relevant art that the compositions, methods and applications described herein may be appropriately modified and adapted without departing from the scope of any embodiment or its aspects. The compositions and methods provided are intended to be used as examples and are not intended to limit the scope of the embodiments. All various embodiments, aspects and options disclosed herein may be combined in all variations. The scope of the compositions, formulations, methods and processes described herein includes all actual or potential combinations of the embodiments, aspects, options and examples herein. Unless other specific incorporation statements are specifically provided, all patents and publications cited herein are incorporated herein by reference for their specific teachings as mentioned.

Claims

1. A method for synthesizing an aluminosilicate zeolite having a silica to alumina ratio (SAR) of 10 or more, the method comprising: forming a reaction mixture comprising at least one alumina source, at least one silica source, and at least one organic structure directing agent, wherein the reaction mixture has a solids content of about 10% or more; and crystallizing the reaction mixture at a temperature of about 100° C. or less at atmospheric pressure in a vessel open to the atmosphere to form the aluminosilicate zeolite, in, Approximately is used to describe fluctuations of less than or equal to ±5%.

2. The method of claim 1, wherein the aluminosilicate zeolite comprises a zeolite having a pore size of 8 rings.

3. The method of claim 1, wherein the aluminosilicate zeolite comprises a zeolite having a framework containing double six-ring (D6r) subunits.

4. The method of claim 1, wherein the aluminosilicate zeolite comprises a zeolite having a framework selected from the group consisting of AEI, AFX, CHA, LEV, AFT, EAB, KFI, SAT, TSC, SAV, ERI, LTA, and combinations of any of the foregoing.

5. The method of claim 1, wherein the aluminosilicate zeolite comprises a zeolite having a CHA crystalline framework.

6. The method of claim 1, wherein the aluminosilicate zeolite has a SAR of 15 or greater.

7. The method of claim 1, wherein the aluminosilicate zeolite has a SAR of 20 or greater.

8. The method of claim 1, wherein the aluminosilicate zeolite has a SAR of 10 to 30.

9. The method of claim 1, wherein the solids content of the reaction mixture is about 15% or more.

10. The method of claim 1, wherein the at least one alumina source comprises a zeolite having a FAU, LTL, LTA, or MOR crystalline framework.

11. The method of claim 10, wherein the zeolite having a FAU crystalline framework is zeolite Y.

12. The method of claim 1, wherein the at least one organic structure directing agent is a quaternary ammonium salt having at least one substituent selected from the group consisting of an alkyl substituent, an aromatic substituent, and a combination of any of the foregoing.

13. The method of claim 1, wherein the at least one organic structure directing agent is tetramethylpiperidinium.

14. The method of claim 1, wherein the temperature ranges from about 95°C to about 100°C.

15. The process of claim 1 wherein the vessel is a stirred vessel equipped with a reflux condenser.

16. The process of claim 1, wherein crystallizing the reaction mixture is carried out under stirring.

17. The method of claim 1, wherein the at least one silica source comprises an alkali metal silicate solution.

18. The method of claim 1, further comprising calcining the aluminosilicate zeolite to form + Form or Na + The calcined zeolite is in the form of.

19. The method of claim 18, further comprising ion exchanging the calcined zeolite with a promoter metal to form an ion-exchanged zeolite catalyst.

20. The method of claim 1, further comprising ion exchanging the aluminosilicate zeolite with a promoter metal to form an ion-exchanged zeolite catalyst.

21. A method according to claim 19 or 20, wherein the promoter metal is Fe or Cu.